Development of a Method for the Synthesis of Ammoniacal Niobium Oxalate Trihydrate for Use as a Precursor in Chemical Reactions - Vitor Manoel Silva Fernandes de Souza; Vinícius Gomes de Sousa Duarte; Kivia Fabiana Galvão Araújo; Maria José dos Santos Lima; Gerlânea Silva Oliveira; Sibele Berenice Castella Pergher; Uilame Umbelino Gomes (Materials Research)
In this project, a method was developed to synthesize ammoniacal niobium oxalate (NH4)(NbO(C2O4)(H2O)ᵧ)·XH2O, aimed at its application in the preparation of niobium-incorporated materials. This transition metal exhibits excellent properties and is widely available in Brazil. Its versatility makes it essential for metal alloys and electronic components. The synthesis was based on physical and chemical processes, including fusion, decantation, filtration, and complexation, using niobium pentoxide and potassium bisulfate. Rigorous procedures were implemented to ensure precursor quality. Material characterization was performed using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), and thermogravimetric analysis (TGA), which collectively confirmed the material's morphology, structure, and thermal stability. The results confirmed the efficient synthesis of high-purity niobium oxalate, with the developed method demonstrating technical feasibility by preserving the material's essential physicochemical properties, as verified by the characterization techniques. Key innovations included replacing acid leaching with a more efficient method, implementing neutral-pH decantation instead of traditional acidic processes, and the strategic use of an aqueous acetic acid solution in the washing step. This combination of advancements enabled a 75% reduction in water consumption during the washing stage, thus establishing a significantly more sustainable synthesis protocol for producing this precursor without compromising final product quality.